Proximal femoral reconstruction after aseptic loosening following proximal femoral replacement for Ewing sarcoma: a case report with one-year follow-up. Issue 1 (January 2014) - Schoof, Benjamin; Jakobs, Oliver; Gehrke, Thorsten; Gebauer, Matthias
We report the case of a 30-year-old patient initially treated for a proximal femoral Ewing's sarcoma when 12 years old. Index treatment comprised tumour resection and total hip arthroplasty. Two years later revision for aseptic loosening was performed. Subsequently, six further surgical revisons were performed for varying causes. At the age of 23 years the proximal femur was resected and a proximal femoral endoprosthesis implanted. Eighteen years after initial diagnosis the patient presented with recurrent aseptc loosening. Both the proximal femur and acetabulum were reconstructed. For acetabular reconstruction a structural allograft and a tantalum cup were utilised. Reconstruction of the femur utilsed extensive wire mesh and circlage wiring with impaction bone allograft into which a femoral stem was implanted. At one-year follow-up the patient was pain free, had no evidence of infection with satisfactory radiographs and no evidence of implant loosening. This is the first case reporting an extended proximal femoral reconstruction with a wire mesh in combination with impaction bone grafting in an aseptic loosened proximal femoral replacement following Ewing's Sarcoma.